2020
DOI: 10.21203/rs.2.16904/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of transcriptomic changes in bovine endometrial stromal cells treated with lipopolysaccharide

Abstract: Abstract Background: Endometritis adversely affects the ability of cattle to reproduce, and significantly reduces milk production. Consequently, it has great influence on the economic value of dairy cows. The endometrium is mainly composed of epithelial and stromal cells and they produce the first immune response to invading pathogens. Epithelial cells are the first cellular barrier through which bacteria enter the uterine endometrium. However, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A greater response of IL-1a than IL-1b and IL-6 relative to controls was observed in LPS treated endometrial cells, suggesting IL-1a aids in upregulating the inflammatory response to LPS (Healy et al, 2014). The IL-17 signalling pathway was also identified as a major inflammatory pathway in LPS stimulation (Ding et al, 2020). The chemokine CCL3 is produced by immune cells, such as macrophages and dendritic cells, to upregulate an inflammatory response by recruiting additional immune cells for LPS clearance (Jing et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A greater response of IL-1a than IL-1b and IL-6 relative to controls was observed in LPS treated endometrial cells, suggesting IL-1a aids in upregulating the inflammatory response to LPS (Healy et al, 2014). The IL-17 signalling pathway was also identified as a major inflammatory pathway in LPS stimulation (Ding et al, 2020). The chemokine CCL3 is produced by immune cells, such as macrophages and dendritic cells, to upregulate an inflammatory response by recruiting additional immune cells for LPS clearance (Jing et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Differences in the expression of LPS binding pattern recognition receptor TLR4 and transcription factor NFkB1 were not detected in LPS treated explants. Previous studies have reported the ability of LPS to increase expression of TLR4, with other studies reporting minimal to no difference between control and LPS challenged tissues, potentially due to differences in LPS concentration and duration of exposure (Cronin et al, 2012;Swangchan-Uthai et al, 2012;Fu et al, 2013;Ding et al, 2020). The TLR4 receptors are present on endometrial tissue, including epithelial and stromal layers, and resident immune cells, such as macrophages, without LPS challenge in preparation for bacterial response (Herath et al, 2006;Dadarwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…endothelial cells and are involved in inflammation and immune functions (51). Each CAM has an inherent effect on the immune response process, such as VCAM-1, which promotes firm binding of T cells and induces transmigration (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript has been released as a preprint at https:// www.researchsquare.com/article/rs-7542/v3, Xuefen Ding, Haimiao Lv, Lixin Deng, Wenju Hu, Zhan Peng, Chenbo Yan, et al (53).…”
Section: Acknowledgmentsmentioning
confidence: 99%